Necrotising fasciitis: a life-threatening complication of acupuncture in a patient with diabetes mellitus - Saw, A.; Kwan, M.K.; Sengupta, S. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2004)
Acupuncture is used for some conditions as an alternative to medication or surgical intervention. Several complications had been reported, and they are generally due to physical injury by the needle or transmission of diseases. We report a case of life-threatening necrotising fasciitis that developed after acupuncture treatment for osteoarthritis of the knee in a 55-year-old diabetic woman. She presented with multiple discharging sinuses over the right knee. As the patient did not respond to intravenous antibiotics, extensive debridement was performed. She made a good recovery. Since many old diabetic patients with degenerative joint diseases may consider this mode of treatment, guidelines on cleanliness and sterility of this procedure should be developed and practiced.